2009
DOI: 10.1179/102453309x12473408860181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori eradication on platelet count in children with chronic idiopathic thrombocytopenic purpura

Abstract: Recent reports have suggested, particularly in adults, an association between Helicobacter pylori infection (HPI) and chronic idiopatic thrombocytopenic purpura (cITP) with improvement of platelet count after eradication therapy. We investigated the association of HPI and cITP and the effect of HP eradication therapy on thrombocytopenia in a population of 24 children of both sexes mean age 8.0+/-0.28 years (range 5.4-10.7 years), affected by cITP (PLT Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
1
24
2
2
Order By: Relevance
“…We also found a significant increase in platelet count of eight patients during six months of follow-up (P < 0.001) compared with the baseline platelet count. This finding was consistent with the findings of other studies (11,12). In the study of Ferrara et al (11) on 24 patients with CITP, eight individuals (33.3%) were infected with H. pylori and eradication treatment was successfully achieved in six out of eight patients with significant increases in platelet count in all six cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also found a significant increase in platelet count of eight patients during six months of follow-up (P < 0.001) compared with the baseline platelet count. This finding was consistent with the findings of other studies (11,12). In the study of Ferrara et al (11) on 24 patients with CITP, eight individuals (33.3%) were infected with H. pylori and eradication treatment was successfully achieved in six out of eight patients with significant increases in platelet count in all six cases.…”
Section: Discussionsupporting
confidence: 82%
“…In the study of Ferrara et al (11) on 24 patients with CITP, eight individuals (33.3%) were infected with H. pylori and eradication treatment was successfully achieved in six out of eight patients with significant increases in platelet count in all six cases. Our findings as well as that of Ferrara et al (11) highlight the effect of H. pylori infection on platelet count in CITP as a basic cause or exacerbation factor. Another study by Sato et al in Japan was performed on 53 patients with CITP (12).…”
Section: Discussionmentioning
confidence: 99%
“…Rajantie et al [29] Finland 0/17 (0) ND Jaing et al [30] Taiwan 9/22 (41) 5/9 (50) Hayashi et al [31] Japan 2/10 (20) 1/1 (100) Yetgin et al [32] Turkey 11/35 (31) 0/9 (0) Jaing et al [33] Taiwan 10/63 (16) ND Loffredo et al [34] Italy 8/39 (21) 0/8 (0) Neefjes et al [35] Netherlands 3/47 (6) 3/3 (100) Wu et al [36] Taiwan 6/32 (19) ND Bisogno et al [37] Italy 8/24 (33) 1/8 (13) Hamidieh et al [38] Iran 4/31 (13) 0/4 (0) Treepongkaruna et al [39] Thailand 16/55 (29) 0/7 (0) Ferrara et al [40] Italy 8/24 (33) 8/8 (100) Maghbool et al [41] Iran 5/30 (17) 5/5 (100) Russo et al [42] Italy 50/244 (20) 13/33 (39) patients in a subgroup of seemingly primary ITP (H. pylori-associated ITP), and H. pylori infection appears to be uninvolved in the pathogenic process of other secondary ITPs.…”
Section: Platelet Responsementioning
confidence: 98%
“…Table 1 summarizes the studies assessing the prevalence of H. pylori infection and platelet response after eradicating H. pylori in children with ITP. Although a Finnish study failed to detect H. pylori infection in any of 17 children with chronic ITP [29] , other studies detected H. pylori infection in a small proportion of children with chronic ITP [30][31][32][33][34][35][36][37][38][39][40][41][42] . The highest prevalence was reported in a study conducted in Taiwan, which showed an infection rate of 41% [29] .…”
Section: Childhood Itpmentioning
confidence: 99%
“…Dies wurde sowohl für Erwachsene als auch für Kinder bestätigt[23]. Man kann die Besserung der Thrombozytenzahl als eine Folge der Eradikationstherapie werten, aber der genaue pathophysiologische Mechanismus ist noch nicht abschließend geklärt.…”
unclassified